O Grupo Multifamília no contexto de vulnerabilidade social: o olhar do profissional - Oliveira, Sonia Maria de (2012)
In order to know and understand the professional experience with the Multifamily Group undertaken in the context of social vulnerability, this research attempted to investigate what is the view of the professional to his group: its composition, the theories and techniques, which use the learning achieved in the relation with the families and what s the influence of the institutional context in the development of his group. Empirical research, of qualitative approach, exploratory descriptive type, used semi structured interviews to collect data. The participants were 05 professional coordinators of Multifamily Group, identified by the criteria of intentional sample. The analysis has been done with a few tools of the qualitative method of Analysis of the Content and the interpretation of the results was based on the theoretical principles of systemic thinking and the new paradigmatic and in the specific literature on the Multifamily Group. The results showed that the prepared professional for such work, should have the needed flexibility to adapt the group to the requirements of the context, without, however, moving away from the defining premises of this practice. His function in the group permeates different tasks; not being possible to adopt a single name to characterize it. The professional performance should preferably be interdisciplinary, backed by legitimated spaces for reflection with other professionals in order to keep a sensitive action to the constructions that may emerge from meetings